Quercetin Inhibits Cell Migration and Invasion in Human Osteosarcoma Cells - Haifeng Lan; Wei Hong; Pan Fan; Dongyang Qian; Jianwei Zhu; Bo Bai (Cellular Physiology and Biochemistry, 2017)
Background/Aims: Osteosarcoma is a malignant tumor associated with high mortality; however, no effective therapies for the disease have been developed. Several studies have focused on elucidating the pathogenesis of osteosarcoma and have aimed to develop novel therapies for the disease. Quercetin is a vital dietary flavonoid that has been shown to have a variety of anticancer effects, as it induces cell cycle arrest, apoptosis, and differentiation and is involved in cell adhesion, metastasis and angiogenesis. Herein, we aimed to investigate the effects of quercetin on osteosarcoma migration and invasion in vitro and in vivo and to explore the molecular mechanisms underlying its effects on osteosarcoma migration and invasion. Methods: Cell viability, cell cycle activity and cell apoptosis were measured using CCK-8 assay and flow cytometry, and cell migration and invasion were evaluated by wound healing and transwell assays, respectively. The mRNA and protein expression levels of several proteins of interest were assessed by real-time quantitative PCR and western blotting, respectively. Moreover, a nude mouse model of human osteosarcoma lung metastasis was established to assess the anti-metastatic effects of quercetin in vivo. Results: We noted no significant differences in cell cycle activity and apoptosis between HOS and MG63 cells and control cells. Treatment with quercetin significantly attenuated cell migration and invasion in HOS and MG63 cells compared with treatment with control medium. Moreover HIF-1α, VEGF, MMP2, and MMP9 mRNA and protein expression levels were significantly downregulated in HOS cells treated with quercetin compared with HOS cells treated with controls. Additionally, treatment with quercetin attenuated metastatic lung tumor formation and growth in the nude mouse model of osteosarcoma compared with treatment with controls. Conclusion: Our findings regarding the inhibitory effects of quercetin on cell migration and invasion suggest that quercetin may have potential as a therapy for human osteosarcoma.